TAM receptors in the pathophysiology of liver disease - Flint,E; Triantafyllou,E; Bernsmeier,C (Livers, 2022)
TAM receptors (Tyro3, Axl and MerTK) are a family of tyrosine kinase receptors that are expressed in a variety of cell populations, including liver parenchymal and non-parenchymal cells. These receptors are vital for immune homeostasis, as they regulate the innate immune response by suppressing inflammation via toll-like receptor inhibition and by promoting tissue resolution through efferocytosis. However, there is increasing evidence indicating that aberrant TAM receptor signaling may play a role in pathophysiological processes in the context of liver disease. This review will explore the roles of TAM receptors and their ligands in liver homeostasis as well as a variety of disease settings, including acute liver injury, steatosis, fibrosis, cirrhosis-associated immune dysfunction and hepatocellular carcinoma. A better understanding of our current knowledge of TAM receptors in liver disease may identify new opportunities for disease monitoring as well as novel therapeutic targets. Nonetheless, this review also aims to highlight areas where further research on TAM receptor biology in liver disease is required.